The comparison study of Chinese and American secondary school students’ knowledge structure—an experimental research based on concept map assessment technique - Zhang, Liping; Wang, Yan; Dong, Boqing; Zhou, Zengyao (Frontiers of education in China, 2009)
A concept map is a schematic device for representing a set of concept meanings embedded in a framework of propositions. It can be used to evaluate students’ knowledge structure. This article introduces the comparative study of Chinese and American secondary school students’ knowledge structure. They are compared quantitatively and qualitatively in terms of mean score, individual proposition scores, proposition choice and map structure. The results indicate that students’ knowledge structures in the two countries are remarkably different. Compared with American students, Chinese students’ ability to take an exam is stronger and their mean score is higher. However, Chinese students need to improve their general knowledge and creativity although their basic knowledge is solid and they are better in mastering discipline knowledge and knowledge application.